Residents' Assessment in Kaligawe Slum Area, Semarang - Maria Ekacarini Jayanimitta; Fadjar Hari Mardiansjah (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
To reduce slum areas, the government of Semarang City has issued a decree of determination of slum areas in 2014 and initiated some slum upgrading activities from the central and local government. Kaligawe, as one of the areas close to the industrial estate and has many residents, is included in a slum area that must be handled. The slum area in Kaligawe consists of 7.35 hectares from RW 1 – RW 4. In addition to the description of the slum characteristics, residents' assessment is also needed regarding the neighborhood condition. This study aims to analyze residents’ assessment in Kaligawe as one of the slum areas in Semarang. This study applied a questionnaire survey that was distributed to 90 residents of Kelurahan Kaligawe slum area randomly from RW 1 – RW 4 and NUAP Kaligawe 2017 document review as the data collection source. The findings indicated that although Kaligawe has a low socioeconomic level, the residents’ assessment of Kaligawe’s neighborhood is overall good. It is because they are already used to live with recent neighborhood conditions, and also significant improvement resulted due to slum upgrading program in Kaligawe area.